Effect of storage in water and thermocycling on hardness and roughness of resin materials for temporary restorations - Oliveira,Jerusa Cleci de (2010)
PURPOSE: This study evaluated the effect of storage in water and thermocycling on hardness and roughness of resin materials for temporary restorations. MATERIAL AND METHODS: Three acrylic resins (Dencor-De, Duralay-Du, and Vipi Cor-VC) were selected and one composite resin (Opallis-Op) was used as a parameter for comparison. The materials were prepared according to the manufacturers' instructions and were placed in stainless steel moulds (20 mm in diameter and 5 mm thick). Thirty samples of each resin were made and divided into three groups (n = 10) according to the moment of Vickers hardness (VHN) and roughness (Ra) analyses: C (control group): immediately after specimen preparation; Sw: after storage in distilled water at 37 °C for 24 hours; Tc: after thermocycling (3000 cycles; 5-55 °C, 30 seconds dwell time). Data were submitted to 2-way ANOVA followed by Tukey's test (α = 0.05). RESULTS: Op resin had higher surface hardness values (p < 0.0001; 25.4 ± 3.4) than the other ones (De = 4.5 ± 0.6; Du = 5.5 ± 0.4; VC = 6.1 ± 0.9). There was no statistical difference (p > 0.05) in roughness among materials (De = 0.31 ± 0.07; Du = 0.51 ± 0.20; VC = 0.41 ± 0.15; Op = 0.42 ± 0.18). Storage in water did not change hardness and roughness of the tested materials (p > 0.05). There was a significant increase in roughness after thermocycling (p < 0.05), except for material Du, which showed no significant change in roughness in any evaluated period (p = 0.99). CONCLUSION: Thermocycling increased the roughness in most tested materials without affecting hardness, while storage in water had no significant effect in the evaluated properties.